2014
DOI: 10.3168/jds.2014-8444
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Factors affecting hair cortisol concentrations in lactating dairy cows

Abstract: Cortisol has long been used as a marker of the stress response in animals. Cortisol can be analyzed from different media, most notably from the blood, saliva, and feces; however, the collection of cortisol from some of these media requires invasive procedures or excessive handling of the animals. Furthermore, it is not possible to capture long-term increases in circulating concentrations of cortisol from the blood, saliva, or feces. Hair cortisol has been found to be a reliable alternative for measuring chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
104
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(131 citation statements)
references
References 30 publications
9
104
3
1
Order By: Relevance
“…The presence of higher cortisol concentrations in black samples in relation with the white ones is in concordance with studies that suggest that number of melanocytes and pigmentation favour the incorporation of lipophilic substances from the bloodstream into the hair (Pötsch et al, 1997;Pragst and Balikova, 2006). However, other studies found higher cortisol concentrations in white hair than in the black ones (González-de-la-Vara et al 2011;Cerri et al, 2012;Burnett et al, 2014). Our contradictory results may be because while the white hair samples were harvested only from the frontal region of the head, the black hair ones were a mixture of hair from frontal region of head and also from the occipital crest.…”
Section: Hair Cortisol Concentrationssupporting
confidence: 74%
See 3 more Smart Citations
“…The presence of higher cortisol concentrations in black samples in relation with the white ones is in concordance with studies that suggest that number of melanocytes and pigmentation favour the incorporation of lipophilic substances from the bloodstream into the hair (Pötsch et al, 1997;Pragst and Balikova, 2006). However, other studies found higher cortisol concentrations in white hair than in the black ones (González-de-la-Vara et al 2011;Cerri et al, 2012;Burnett et al, 2014). Our contradictory results may be because while the white hair samples were harvested only from the frontal region of the head, the black hair ones were a mixture of hair from frontal region of head and also from the occipital crest.…”
Section: Hair Cortisol Concentrationssupporting
confidence: 74%
“…Thus, black hair samples were homogeneous in colour but not in location and so, hair type. The authors did not find any study comparing cortisol concentrations from these two close regions but other studies found differences in hair cortisol levels among other locations (Cerri et al, 2012;Moya et al, 2013;Burnett et al, 2014). Hair from the occipital crest in Holstein-Friesian cows is longer and thicker than hair from frontal region and studies performed by Burnett et al (2014) and Moya et al (2013) found higher cortisol concentrations in locations where hair type was also longer and thicker (especially the tail switch).…”
Section: Hair Cortisol Concentrationsmentioning
confidence: 50%
See 2 more Smart Citations
“…Hair cortisol concentration therefore has evolved as a novel biomarker for chronic stress in humans (Russel et al, 2012). There have been several studies on hair cortisol concentrations in healthy and ill cattle (González-de-la-Vara et al, 2011;Comin et al, 2011Comin et al, , 2012Comin et al, , 2013Peric et al, 2013;Burnett et al, 2014Burnett et al, , 2015; ill cattle have higher concentrations than healthy cattle Burnett et al, 2015). To the authors' knowledge, there have been no studies comparing adrenal gland weight and hair cortisol concentrations in cattle.…”
Section: Introductionmentioning
confidence: 95%